The effects of offering flexible work practices to employees with unpaid caregiving responsibilities for elderly or disabled family members - Bainbridge, Hugh T. J.; Townsend, Keith (Human Resource Management, 2020)
AbstractApproximately one in 10 employees in Australia, the United States, and Europe have unpaid caregiving responsibilities for elderly or disabled family members. This combination of employment and caregiving roles is problematic when there is conflict between their simultaneous demands. Flexible work practices can be an important mechanism for assisting these employees. However, limited attention has been given to determining the benefits of flexible work practices for these employees, or the process by which these effects arise. We address these gaps via a survey of employees with unpaid caregiving responsibilities for family who are elderly or disabled. Results indicate that greater availability of flexible work practices improves perceptions of workplace support for combining caregiving and employment. This effect was partially and sequentially mediated by disclosure, practice utilization, and practice helpfulness. Additionally, practice availability had a direct positive effect on practice utilization, while disclosure had a direct positive effect on perceived support. Overall, the findings demonstrate the benefits of flexible work practices for employees with caregiving responsibilities. The study also points the way to interventions that can improve the effectiveness of flexible work practices by demonstrating how the potential benefits of these practices are translated into actual improvements in perceived support.